MELAS in Latin America - Aguirre-Quispe, Wilfor (2022)
A thematic review on MELAS in Latin America between 1990 and 2021 was conducted through a systematic literature search on LILACs, Scielo, PubMed/Medline and Scopus databases. Nineteen case reports/series out of 966 publications were selected and included 51 patients, 42 of them with genetic diagnosis reported in eight Latin American countries. The m.3243A> G variant was the most frequently reported, the mean age at onset being 12 ± 9.7 years, with a mild female predominance. The most frequent neurological features were stroke-like episodes and seizures. Neuroimaging tests highlighted ischemic stroke-like lesions as well as calcified lesions in the basal ganglia.